The role of traditional livelihood practices and local ethnobotanical knowledge in mitigating chestnut disease and pest severity in Turkey - Wall, J.; Köse, C.; Köse, N.; Okan, T.; Aksoy, E.B.; Jarvis, D.; Allred, S. (MDPI, 2019)
The European chestnut population is enduring multiple compounding exotic pest and disease outbreaks across Turkey. The deeply held value of the chestnut species for the Turkish public is reflected in substantial government conservation programming. Chestnut is predominantly found on state land managed by Turkey’s General Directorate of Forestry (GDF), which generally upholds restrictive policies for chestnut-related livelihood practices other than nut collection and beehive placement. Such policies are justified by a government position that human activities and presence is likely to worsen disease dynamics. Conversely, a growing body of research findings testify that small-scale livelihood practices maintain biological diversity and, furthermore, that this traditional maintenance of diversity has been correlated with decreased pathogen pressure within agroecosystems. However, few studies have investigated this phenomenon in the context of agroforestry systems. At a global ecological moment of increasingly pervasive and severe exotic forest pathogen impact, this paper investigates the influence of diverse small-scale livelihood practices and knowledge on chestnut tree health across the highly heterogenous geography of Turkey. We conducted ethnobotanical questionnaires with 96 chestnut-utilizing households, and chestnut tree health evaluations in georeferenced forest areas they identified, throughout Turkey’s Black Sea, Marmara, and Aegean regions. Using data from 1500 trees, we characterized the effects of subsequently recorded environmental, physiological, and anthropogenic factors on tree health using multiple correspondence analysis (MCA), multiple factor analysis (MFA), and mixed models. Our results show that the traditional human management of tree physiology and ecology has a significant positive effect on tree health, especially through the acts of grafting and culling as well as the maintenance of diversity. We argue that conceptualizing such livelihood systems as human niche construction and maintenance can help forest management agencies to better understand and conserve valuable landscapes, even in increasingly common periods of severe pathogenic pressure.